Pendidikan Pesantren di Zaman Teknologi antara Tradisi dan Modernitas - Kurniawati, Wakhidah; Anshory, Muhammad Isa (Lembaga Yasin AlSys, 2024)
Islamic boarding schools, as traditional Islamic educational institutions, have become an integral part of the history of education in Indonesia. However, with the emergence of modern technology, Islamic boarding schools are faced with new challenges that require adaptation to current developments. This article explores the dynamics of Islamic boarding school education in facing the technological era, exploring how these institutions try to maintain traditional values while still taking advantage of technological advances. This research was conducted using a qualitative approach with in-depth interviews and participant observation at several leading Islamic boarding schools. The findings show that Islamic boarding schools face a dilemma between preserving traditions and responding to the demands of the times. Several Islamic boarding schools have succeeded in integrating technology into their curriculum without sacrificing fundamental Islamic values. However, challenges in managing the impacts of modernity are also visible, including the potential for changes in social and spiritual values among santri. This article provides insight into Islamic boarding schools' efforts to bridge the gap between tradition and modernity. The practical and strategic implications of this research can provide guidance for Islamic boarding schools and other stakeholders in developing education that is relevant to the times without losing the essence of Islamic boarding school education which has become a characteristic of educational culture in Indonesia.